Islamization in Pakistan: A Need to Focus on Promoting a Tolerant Society Pengislaman Di Pakistan: Satu Refleksi Mengenai Isu- Isu yang Berkaitan - Abbasi, Manzoor Ahmed; Islam, Muqeem ul (Journal of Islam in Asia (E-ISSN 2289-8077), 2014)
Abstract The issue of incorporation of Islamic provisions in the constitutional, legal, economic, socio-political order as well as policy structures of the Government of Pakistan emerged on the policy agenda in the last years of Pakistan movement and immediately after independence. This issue, commonly known as ‘Islamization’, however, remained a hotly debated topic. Undoubtedly, Islam, as a way of life and the embodiment of universal human values of social justice, tolerance, and equity was the most motivating and inspiring factor in the struggle for creation of Pakistan. It was believed that the enormity of the task of re-construction of Islamic thought notwithstanding, it would not be beyond the resources of Pakistan to convert itself into model Islamic welfare state, where all citizens, irrespective of their caste, colour, language or creed, would live in an atmosphere of tolerance and harmony. It was unfortunate that Pakistan, despite the lapse of 67 years, could not promote an enlightened and tolerant society. The policy debate in connection with the issue of Islamization should, therefore, be directed towards the promotion of a society which should be more tolerant, just, equitable and prosperous. It would, in turn, require the evolution of a balanced and uniform system of education, in which the existing religious stream of education i.e. ‘Madaris’ should also be integrated. The paper in hand aims at analyzing the dynamics of Islamization, as a policy perspective, with a view to identifying the direction of policy debate that should take place in the policy-making institutions about this issue. Keywords: Islamization, Mainstreaming, Tolerant-society, Weltanschauung, Justice, Equity. ******************** Abstrak Isu perintah pemerbadanan peruntukan Islam di perlembagaan, perundangan, ekonomi, sosio-politik dan struktur polisi Kerajaan Pakistan muncul dalam agenda polisi pada tahun-tahun terakhir pergerakan Pakistan dan sejurus selepas kemerdekaan mereka. Isu ini, biasanya dikenali sebagai ’Pengislaman’, bagaimanapun, kekal sebagai topik hangat. Tidak dinafikan, Islam, sebagai satu cara hidup dan penjelmaan nilai-nilai manusia sejagat bagi keadilan sosial, toleransi, dan ekuiti adalah faktor motivasi dan inspirasi yang paling penting dalam perjuangan untuk penciptaan Pakistan. Ia dipercayai bahawa kebesaran tugas pembangunan kembali pemikiran Islam, walau apa pun, ia tidak akan melebihi keupayaan sumber Pakistan untuk menukar dirinya menjadi satu model negara kebajikan Islam, di mana semua rakyat, tanpa mengira kasta, warna kulit, bahasa atau fahaman , akan hidup dalam suasana bertoleransi dan keharmonian. Ia sangatlah malang bahawa Pakistan, walaupun luput 67 tahun, tidak boleh menggalakkan masyarakat untuk berpengetahuan dan bertoleran. Perdebatan dasar berkaitan dengan isu pengislaman harus, oleh itu, ditumpukan ke arah menggalakkan masyarakat untuk lebih toleran, adil, saksama dan makmur. Ia akan, seterusnya, memerlukan evolusi sistem yang seimbang dan sekata bagi pendidikan, di mana arus pendidikan agama yang sedia ada yakni ’Madaris’ juga perlu bersepadu. Karya ini bertujuan untuk menganalisisasi kedinamikan pengislaman, sebagai perspektif polisi, dengan tujuan untuk mengenal pasti arah perdebatan polisi yang perlu mengambil tempat dalam institusi pembuat polisi mengenai isu ini. Kata Kunci: Pengislaman, Mainstreaming, Masyarakat Bertoleran, Weltanschauung, Keadilan, Saksama.